2004
DOI: 10.1021/bi0483864
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of an Unnatural Difluorophenyl Nucleotide by Uracil DNA Glycosylase

Abstract: The DNA repair enzyme uracil DNA glycosylase (UDG) utilizes base flipping to recognize and remove unwanted uracil bases from the genome but does not react with its structural congener, thymine, which differs by a single methyl group. Two factors that determine whether an enzyme flips a base from the duplex are its shape and hydrogen bonding properties. To probe the role of these factors in uracil recognition by UDG, we have synthesized a DNA duplex that contains a single difluorophenyl (F) nucleotide analogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The lower limit for k C was determined to be 1715 s −1 , which is much faster than the rates of spontaneous base pair opening in a regular B-DNA molecule (44,45). The situation resembles base flipping by the DNA repair enzyme uracil DNA glycosylase (46).…”
Section: N+6 Dc-matchmentioning
confidence: 95%
“…The lower limit for k C was determined to be 1715 s −1 , which is much faster than the rates of spontaneous base pair opening in a regular B-DNA molecule (44,45). The situation resembles base flipping by the DNA repair enzyme uracil DNA glycosylase (46).…”
Section: N+6 Dc-matchmentioning
confidence: 95%
“…Structural studies have been performed with antibiotics bound to cell walls or whole cells, typically prepared in trehalose-or ethanolamine-based lyophilization buffers, wherein trehalose serves as an effective hydrogen bonding partner as bulk water is removed during lyophilization. Such lyophilized formulations have permitted structure-based studies of enzymes such as lumazine synthase [42], EPSP synthase [43], factor Xa [44] and uracil DNA glycosylase [45], and are not perturbative to structure. The enzymes can maintain their enzymatic activity even after NMR measurements upon sample rehydration and assay.…”
Section: (D) Nmr Sample Preparationmentioning
confidence: 99%
“…In spite of extensive kinetic and structural investigations, the mechanisms of base-flipping and base stabilization, and their importance to rate enhancements and specificity generation, remain ambiguous. [24][25][26][27] We have shown that Val121 in M.HhaI, positioned immediately above the flipped-out cytosine ( Figure 1(b)), is extremely important for initiating and/or maintaining the flipped state. 23 Replacement of Val121 with alanine results in a 10 5 -fold loss of DNA affinity, which is recovered entirely when the mutant is presented with DNA lacking a base at the target cytosine position.…”
Section: Introductionmentioning
confidence: 96%